Revision arthroplasty with megaprosthesis after Girdlestone procedure for periprosthetic joint infection as an option in massive acetabular and femoral bone defects.: Revision arthoplasty after girdlestone procedure - Piscopo, Antonio; Pola, Enrico; Fusini, Federico; Cipolloni, Valerio; Piscopo, Davide; Colò, Gabriele; Zanchini, Fabio (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: To evaluate the clinical outcomes of patients treated with Girdlestone procedure (GP) or excision arthroplasty (EA) for periprosthetic infection with massive bone defects and undergoing revision arthroplasty. Methods: All patients treated with EA or GP for hip periprosthetic infection between 2014 and 2017 and sustaining revision arthroplasty (RA) were included in the study. Patients with less than 24 months of follow-up or less than 12 months between GP or EA and RA were excluded. Any sign of implant mobilization or periprosthetic fracture was assessed through X-ray. Patients were evaluated with D’aubignè-Postel hip score before RA and at the last follow-up. Mann-Whitney U test was used to assess differences between pre-RA surgery and last follow-up. P value was set as <0.05. Results: Twelve patients meet the inclusion criteria (mean follow-up 58+/-9.72 months). No radiographic sign of implant mobilization or periprosthetic fracture was reported. A significant difference was found for each parameter of the D’Aubigne-Postel score (p < 0.0001); none of the patients reached more than fair results in the absolute hip score. The difference between pre and post-operative global status showed a fair improvement. A significant difference was found for leg length discrepancy between pre and post RA (p<0.0001). Conclusions: Conversion from EA or GP to RA in patients suffering from massive acetabular and femur defects is challenging; conversion procedure is able to reduce patients’ disability and to improve walking ability. (www.actabiomedica.it)